Family Education Starts from Empowering Women in Communities: Seeing from the Relationship between Self-Acceptance, Happiness, and Work-Family Balance - Rahmawati Rahmawati; Mokete Nyaphisi; Mohamad Saripudin (Universitas Sultan Ageng Tirtayasa, 2021)
This research aims to know the relationship between self-acceptance, happiness, and work-family balance on the empowerment of communities. The respondents of this study were 54 women in Serang City, Banten Province, Indonesia. Sampling by purposive sampling with restrictions on the subject of women, married, living in a single house with a partner, living with the nuclear family. The procedure of collecting data by summated rating method. The scale of self-acceptance, happiness, and WFB. From F-test there are values F = 43.28; R = 0.793 (> 0.5) with p = 0.001 (<0.01), there are positive meaning relationships between self-acceptance and happiness with WFB. Partially from the t-test, the scale of self-acceptance of WFB obtained a value of R = 0.747 and p = 0,000 (<0.01), meaning there is a positive relation between self-acceptance and WFB. Adjudication whereas from happiness to WFB obtained the value of R = 0.739 and p = 0.007 (<0.01), meaning there is a positive relationship between the happiness of WFB.